2019
DOI: 10.1177/1043659619856667
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the “Hard-to-Reach”: Recruitment of Rural-Dwelling Adults With Disabilities

Abstract: Introduction: There are 46 million individuals living in rural America that require unique consideration for rural health research. Recruitment of research participants from disparity groups can be difficult as these groups can be hard-to-reach. In particular, strategies for reaching rural-dwelling Americans with disabilities are not well-documented. Furthermore, researchers sometimes underestimate the time and effort needed to recruit participants from hard-to-reach populations. The purpose of this article is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…In line with the literature, we found that older patients with a higher SES [ 18 ] and male [ 45 ] patients were more likely to participate. Further research focussing on non-responders is needed to gain more insights into barriers and potential facilitators for participation to implement recruitment strategies tailored to these more difficult-to-reach patients [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the literature, we found that older patients with a higher SES [ 18 ] and male [ 45 ] patients were more likely to participate. Further research focussing on non-responders is needed to gain more insights into barriers and potential facilitators for participation to implement recruitment strategies tailored to these more difficult-to-reach patients [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited through community gatekeepers such as church staff and Veterans’ Services Officers, newspaper classified advertisements, word-of-mouth, and professional networks. Sampling and recruitment methods are detailed elsewhere (Thurman & Harrison, Manuscript under review). Participants were offered US$25 for participating in each interview.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of having a multicultural team is underappreciated and underutilized in current research practices (Thurman & Harrison, 2020). In fact, the lack of a multicultural team is a social and ethical issue (Mcauliffe, Grothaus, Jensen, & Michel, 2012).…”
Section: Research Team Compositionmentioning
confidence: 99%
“…Internal diversity supports the highest regard for intercultural communication. It promotes maximum outcomes for observing professional and personal skills in communication and language and provides motivation to participate for those participants from hard-to-reach populations (Thurman & Harrison, 2020).…”
Section: Research Team Compositionmentioning
confidence: 99%
See 1 more Smart Citation